POLITIK TRANSAKSIONAL DALAM PILKADA SERENTAK DAN IMPLIKASINYA BAGI PEMERINTAHAN DAERAH DI INDONESIA - Ratnia Solihah (Magister Ilmu Politik Universitas Hasanuddin, 2016)
Simultaneous implementation of the election already held on 9 December 2015, essentially is an alternative system of direct local elections in order to save significant budget of budget execution during the election is charged to the budget. But in its implementation, simultaneous election in 2015 was allegedly gave birth to the various phenomena associated with transactional politics that emerged in the process of election.This paper prepared using descriptive method through a qualitative approach. The data collection is done by using study of literature through the study of literature related to the phenomenon of transactional politics in the election simultaneously in Indonesia in 2015, and its implications for government formed from the election process.Concurrent election implementation in 2015 gave rise to various phenomena associated with transactional politics that political barter, stuffed politics, politics of high costs, and the existence of money politics in voting behavior. In general, transactional politics injure the realization of democratic elections and the implications for the process of the election itself less democratic. In particular, the transactional politics that can bring the seeds of mistrust support to political parties and may confuse its supporters over the choice of a political party, led to the behavior of corrupt government officials, and local autonomy are not positively correlated to improving the welfare and quality of life of the people.